The Effect of Creative Thinking on Strategic Flexibility: A Field Study on Administrative Leaders at the Libyan Iron and Steel Company in Misurata (Abhat Journal, 2025)
This study examines the effect of creative thinking on strategic flexibility at the Libyan Iron and Steel Company in Misrata city. It also aims to measure the levels of creative thinking and strategic flexibility among the company’s administrative leadership. The study adopted a descriptive methodology. The data was collected quantitatively and qualitatively through a questionnaire. The population consisted of 213 administrative leaders. The sample consisted of 137 participants and it was selected through a purposive sampling technique following Krejcie and Morgan’s (1970) table. A total of 133 valid responses were obtained (97% response rate). Data were analyzed using SPSS. The results revealed a high level of creative thinking (mean = 3.8439) across its dimensions and a high level of strategic flexibility (mean = 3.8626). The study recommends leveraging these high levels to develop strategies that enhance the company’s adaptability, particularly in the light of Libya’s volatile political and economic situation
Keywords: Creative Thinking; Strategic Flexibility; Libyan Iron and Steel Company in Misrata Municipality